The influence of two South African fly ashes on the engineering properties of concrete. - Grieve, Graham Robert Hugh. (My University, 1991)
The South African cement producers would like to utilise cement extenders in cement to increase manufacturing capacity at a relatively low cost. A" understanding of the implications such a step might have for the cement user was required. A study was made of the performance of portland cement blends made with fly ash derived from the two commercial sources in South Africa that were being utilised by 1991. The performance of the blends was compared against the performance of ordinary portland cement, the cement type to which the majority of users in South Africa were exposed in the past. An extensive literature study was provided which covered the latest research aspects .ot the use of fly ash in many other parts or the world as well as mformation from local South African research reports. The ash concrete or mortar properties studied in the laboratory tests were as follows: • workability • rheology • setting time bleeding • heat of hydration The following properties of hardened concrete were studied in laboratory and simulated site exposure tests: • compressive strength flexural strength elastic modulus • shrinkage • creep • permeability • abrasion resistance • carbonation Some preliminary investigations were made into the effect that the use of fly ash had on the effectiveness of chemical admixtures, and into the compressive strength development of ternary (three component) blends. As far as possible, use was made of standard SABS, BS, ASTM, DIN or RILEM test methods although it was necessary to use other non-standard or modified test methods in some cases to provide the necessary information. Appropriate references or details have been provided where methods have deviated from standard methods. Recommendations were made regarding the level of fly ash replacement which was believed to be practical for site use for two categories of users, nameiy unsophisticated users with a low !evel of understanding of concrete technology and relatively crude methods of site batching and mixing, and sophisticated users with access to higher levels of technology and equipment.
A thesis submitted to the Faculty of Engineering, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Doctor of Philosophy.
Keywords: Concrete -- Additives.; Portland cement -- Additives -- South Africa.; Cement -- Additives.; Fly ash.